Digital Leadership towards Performance Through Mediation of Organizational Commitment to E-commerce in Indonesia - Ahmad Gunawan; Tjutju Yuniarsih; A Sobandi; Sambas Ali Muhidin (Pandawan, 2023)
Entrepreneurs with a strong digital focus were crucial to the development of the e-commerce industry in Indonesia. Some online stores' sales have slowed or even declined as a result of the industry's meteoric rise in recent years. Therefore, remedies are required to ensure the long-term health and growth of e-commerce results. The Purpose of this study to search Solutions to this performance issue are sought in this study by examining the relationships between digital leadership, organizational commitment, and performance, three factors that have received much attention from the academic community. Research method used in the study, a quantitative approach was applied. An electronic questionnaire was circulated via the internet in a snowball pattern, yielding the data used in the study. There were 150 high-level employees and managers from market-place businesses who participated in this survey.According to the result of the study, digital leadership does not have a significant impact on performance factors, but it does have a large impact on organizational commitment. On the other hand, organizational commitment does have a substantial impact on performance variables. It has been determined that digital leadership has a considerable effect on performance factors through the mediation of organizational commitments, which leads to the conclusion that indirect interactions are involved. In these findings, it is necessary to increase commitment so that the company's performance can increase and ultimately achieve company goals.